P‐Doped SiOx/Si/SiOx Sandwich Anode for Li‐Ion Batteries to Achieve High Initial Coulombic Efficiency and Low Capacity Decay (Small Methods 3/2022). Issue 3 (21st March 2022) - Im, Jinsol; Kwon, Jung‐Dae; Kim, Dong‐Ho; Yoon, Sukeun; Cho, Kuk Young
Abstract : Inside Front Cover In article number 2101052, Kim, Yoon, Cho, and co‐workers provided new sandwich‐structured trilayer Si thin‐film anodes demonstrating enhanced electrical conductivity and Li‐ion diffusion coefficient from the synergy between structural properties and P‐doping. Consequently, a Si anode with the highest initial Coulombic efficiency of 90.4% is achieved, thereby exhibiting superior electrochemical properties as anode material for advanced Li‐ion batteries.